Virtual Physics Experiments: Transforming Science Process Skills Through Digital Integration - Syukriah*, Syukriah; Evendi, Evendi; Zainuddin, Zainuddin; Syukri, Muhammad; Subramaniam, Tamil Selvan (Jurnal IPA & Pembelajaran IPA, 2025)
This research is motivated by the limited infrastructure of physics laboratories in educational institutions and students science process skills (SPS) which are still in the low category. This study examines the effectiveness of implementing virtual laboratory-based worksheets in improving four main indicators of SPS: the ability to formulate problems, formulate hypotheses, identify variables, and design experiments. This study is a quasi-experimental study with a one-group pretest-posttest design involving 35 grade XI students of SMA Negeri 1 Kota Langsa. The research instrument is in the form of validated pretest and posttest questions, compiled based on the four indicators of SPS being studied. Data analysis uses the N-gain test to measure the increase in the ability of each indicator of SPS. The results of the study showed a significant increase in all indicators of SPS with N-gain values: identifying variables (0.92; high category), designing experiments (0.69; medium category), formulating problems (0.56; medium category), and formulating hypotheses (0.53; medium category). These findings confirm that virtual laboratory based worksheets are effective as an alternative to physics learning in developing students SPS. This study recommends the implementation of virtual laboratories as an innovative solution to overcome the limitations of conventional laboratory facilities and support digital transformation in science education